The Metropolitan Area of the Municipality of Bucharest. Present-Day Features Relating to Some Environmental Issues in an International Context - INES GRIGORESCU; DAN BĂLTEANU (Romanian Review of Regional Studies, 2005)
The development of metropolitan areas represents the main characteristic of today’s urban evolution trends. The first initiatives to delimitate and define metropolitan areas have been in the United States since 1910. In Europe, this concept was adopted at the beginning of the1990s when the United States had already had 250 metropolitan areas. Romania adopted the concept of metropolitan area in the late 1990s, namely in 1997 when a study on the Directions, Ways, and Intensities of Development in the Municipality of Bucharest and its Metropolitan Zone. Environmental protection politics appeared. This made public a point of view about the Bucharest metropolitan area, which was legally defined by Law no. 351 of July 6th 2001 regarding the National Territory Management Plan, Section IV – Settlements. But many other limits of this area were also taken into account. The uncontrolled evolution of the Bucharest Metropolitan Area as well as of many other European capital cities can be stopped or stabilized by developing green belts or green areas.